2015
DOI: 10.1105/tpc.15.00395
|View full text |Cite
|
Sign up to set email alerts
|

Remobilization of Phytol from Chlorophyll Degradation Is Essential for Tocopherol Synthesis and Growth of Arabidopsis

Abstract: Phytol from chlorophyll degradation can be phosphorylated to phytyl-phosphate and phytyl-diphosphate, the substrate for tocopherol (vitamin E) synthesis. A candidate for the phytyl-phosphate kinase from Arabidopsis thaliana (At1g78620) was identified via a phylogeny-based approach. This gene was designated VITAMIN E DEFICIENT6 (VTE6) because the leaves of the Arabidopsis vte6 mutants are tocopherol deficient. The vte6 mutant plants are incapable of photoautotrophic growth. Phytol and phytyl-phosphate accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(182 citation statements)
references
References 45 publications
4
169
0
1
Order By: Relevance
“…The chlorophyll degradation pathway has recently been elucidated in Arabidopsis (Schelbert et al, 2009;Hörtensteiner and Kräutler, 2011;Hörtensteiner, 2013) (Figure 4C), and the phytol released from pheophytin a by pheophytinase could be esterified to fatty acids to yield fatty acid phytyl esters or phosphorylated by VTE5 and VTE6 to yield phytyl-DP (Valentin et al, 2006;Tanaka et al, 2010;DellaPenna and Mène-Saffrané, 2011;Lippold et al, 2012;Zhang et al, 2014;Vom Dorp et al, 2015) (Figure 4C). This latter route clearly provides phytyl-DP for the large amounts of tocopherol synthesized by senescing Arabidopsis leaves, as mutation of the pheophytinase gene eliminates both chlorophyll degradation and the senescence-associated increases in tocopherol and fatty acid phytyl ester levels (Schelbert et al, 2009;Zhang et al, 2014;Vom Dorp et al, 2015). If flux through this chlorophyll degradation pathway provided the majority of phytol for tocopherol biosynthesis in other tissues and leaf development stages, one would expect a similarly severe impact on tocopherol levels in these tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chlorophyll degradation pathway has recently been elucidated in Arabidopsis (Schelbert et al, 2009;Hörtensteiner and Kräutler, 2011;Hörtensteiner, 2013) (Figure 4C), and the phytol released from pheophytin a by pheophytinase could be esterified to fatty acids to yield fatty acid phytyl esters or phosphorylated by VTE5 and VTE6 to yield phytyl-DP (Valentin et al, 2006;Tanaka et al, 2010;DellaPenna and Mène-Saffrané, 2011;Lippold et al, 2012;Zhang et al, 2014;Vom Dorp et al, 2015) (Figure 4C). This latter route clearly provides phytyl-DP for the large amounts of tocopherol synthesized by senescing Arabidopsis leaves, as mutation of the pheophytinase gene eliminates both chlorophyll degradation and the senescence-associated increases in tocopherol and fatty acid phytyl ester levels (Schelbert et al, 2009;Zhang et al, 2014;Vom Dorp et al, 2015). If flux through this chlorophyll degradation pathway provided the majority of phytol for tocopherol biosynthesis in other tissues and leaf development stages, one would expect a similarly severe impact on tocopherol levels in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations with chlorophyllide a and chlorophyll b with total tocopherols gradually decreased to r = 0.48 and r = 0.36, respectively, at 30 DAP, after which chlorophyll b correlation increased. Pheophytin a is a key intermediate and metabolite marker for the chlorophyll degradation pathway in senescing leaves (Schelbert et al, 2009;Hörtensteiner and Kräutler, 2011;Hörtensteiner, 2013), where it provides phytol for senescence-associated tocopherol biosynthesis (Schelbert et al, 2009;Zhang et al, 2014;Vom Dorp et al, 2015), but pheophytin a only showed weak correlations with total tocopherols at 16 and 20 DAP (r = 0.23 and 0.31, respectively) and was negatively correlated at later developmental stages. Tocopherols accumulated in endosperm to levels <2% that in embryos, and endosperm chlorophyll metabolite levels were similarly reduced, with only chlorophyll a being consistently above the limits of detection (Supplemental Data Set 9; Figure 4B).…”
Section: The Role Of a Priori Pathway Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the light-harvesting-like proteins LIL3:1 and LIL3:2 were shown to be involved in tocochromanol metabolism through their interaction and stabilization of GGR proteins in the chloroplast membrane [19]. In Arabidopsis seeds and leaves, tocopherol synthesis mostly depends on the phytol kinase VTE5 and the phytyl phosphate kinase VTE6 that sequentially phosphorylate phytol into PPP [20,21 ]. In senescent leaves, the phytol used for tocopherol synthesis originates mostly from chlorophyll hydrolysis [21 ].…”
Section: Update On the Tocochromanol Biosynthetic Pathwaymentioning
confidence: 99%
“…In Arabidopsis seeds and leaves, tocopherol synthesis mostly depends on the phytol kinase VTE5 and the phytyl phosphate kinase VTE6 that sequentially phosphorylate phytol into PPP [20,21 ]. In senescent leaves, the phytol used for tocopherol synthesis originates mostly from chlorophyll hydrolysis [21 ]. In Arabidopsis seeds, chlorophyll degradation and recycling contributes at least 60% to tocopherol synthesis [20].…”
Section: Update On the Tocochromanol Biosynthetic Pathwaymentioning
confidence: 99%